Necessity of facial contouring in feminization surgery for Chinese transgender females - Li, Dong (Ann Transl Med, 2021)
BACKGROUND: An increasing number of transgender females are suffering from a critical gender dysphoria, which often presents as depression and self-destructive behavior. Facial feminization surgery (FFS) is an effective method to alleviate symptoms of gender dysphoria, which could be more important than genital reassignment surgery for Chinese. Facial contour surgery is perceived as an ordinary FFS for the Chinese women to improve their facial appearance. The zygoma and jaw are key areas for feminizing the facial contour. This study mainly emphasized the necessity of FFS and discussed the importance of facial contour surgery of Chinese individuals. METHODS: The differences of facial contour before and after FFS in terms of skeletal and soft tissue were analyzed. The pre- and postoperative images were evaluated for feminization. The results of the full suite of measurements were compared to reveal the effective change of FFS. Furthermore, a surgery satisfaction survey was conducted among these patients after recovery. RESULTS: All the patients expressed their satisfaction with the reduction in the intergonial width as well as the middle face prominence. All the facial contour ratios changed significantly after surgery in both hard tissue and soft tissue. CONCLUSIONS: Facial contour surgery is crucial to changing one’s facial appearance and sex impression, which significantly alleviates gender dysphoria.